2010
DOI: 10.1111/j.1365-2729.2010.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of MMORPG‐based instruction in elementary English education in Korea

Abstract: This study investigated the effectiveness of massive multiplayer online role-playing game (MMORPG)-based (massive multiplayer online role-playing game) instruction in elementary English education. The effectiveness of the MMORPG program was compared with face-toface instruction and the independent variables (gender, prior knowledge, motivation for learning, self-directed learning skills, computer skills, game skills, computer capacity, network speed, and computer accessibility) were examined to see how accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(96 citation statements)
references
References 18 publications
1
81
1
4
Order By: Relevance
“…Among the constructs of language learner strategies, however, the only construct having a statistically significant effect on achievement test scores was metacognitive strategies. Suh et al (2010) investigated the effectiveness of massive multiplayer online roleplaying game (MMORPG)-based (massive multiplayer online role-playing game) instruction in elementary English education. The results indicated that students studying English utilizing online role-playing games showed higher scores in areas of listening, reading, and writing than those who attended face-to-face instruction classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the constructs of language learner strategies, however, the only construct having a statistically significant effect on achievement test scores was metacognitive strategies. Suh et al (2010) investigated the effectiveness of massive multiplayer online roleplaying game (MMORPG)-based (massive multiplayer online role-playing game) instruction in elementary English education. The results indicated that students studying English utilizing online role-playing games showed higher scores in areas of listening, reading, and writing than those who attended face-to-face instruction classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, research on MMORPGs (the game genre most played by participants) proposes that such games can help improve learners' second language learning (e.g., Rama, Black, van Es & Warschauer, 2012), such as English learning (Suh, Kim & Kim, 2010). Moreover, the default language of communication in many games is English and therefore it is accepted that successful and frequent players of such games that do not have English as their mother tongue acquire some of their…”
Section: Discussionmentioning
confidence: 99%
“…Network-based games can assist in language competencies for ESL learners through the opportunities of social interaction and collaborative communications with peers (Ang & Zaphiris, 2007;Peterson, 2010). Other studies relate to examining the effects of prior knowledge on English proficiency gains using MMOGs (Huang & Yang, 2014;Lee & Pass, 2014;Liu, Yang & Huang, 2012;Yang & Hsu, 2013), using MMOGs in elementary English education to increase listening, reading, and writing scores of experimental groups (Suh, Kim & Kim, 2010), safe learning spaces for ESL that MMOGs can provide (Kongmee, Strachan, Pickard & Montgomery, C, 2011), and the ability of MMOGs to inspire students to write more prolifically (Martin, 2011).…”
Section: Introductionmentioning
confidence: 99%